PERAN KOMITMEN AFEKTIF DAN EMOTIONAL EXHAUTION TERHADAP TURNOVER INTENTION - Adistira Fikri Ananta Harun; Resa Nurmala; Sopyan Saori (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of affective commitment and emotional exhaustion on turnover intention among Alfamart employees in Sukabumi City. This research employed a quantitative approach with descriptive and associative methods. The sample consisted of 39 Alfamart employees selected using purposive sampling, with the criteria of being active employees, domiciled in the Sukabumi area, and having at least one year of work experience. Data were collected through observation, interviews, questionnaires, documentation, and literature study. The data were analyzed using validity and reliability tests, classical assumption tests, correlation coefficient, coefficient of determination, multiple linear regression, t-test, and F-test with SPSS. The results show that affective commitment has a significant effect on turnover intention, with a t-value of 2.165 > t-table 1.687 and a significance value of 0.000 < 0.05. Emotional exhaustion also has a significant effect on turnover intention, with a t-value of 12.033 > t-table 1.687 and a significance value of 0.000 < 0.05. Simultaneously, affective commitment and emotional exhaustion significantly affect turnover intention, as indicated by an F-value of 88.897 > F-table 3.28. The coefficient of determination of 0.839 indicates that both variables explain 83.9% of turnover intention. These findings indicate that strengthening affective commitment and managing emotional exhaustion are necessary to reduce employees’ intention to leave the organization.